Analisis Kemampuan Literasi Membaca Anak Usia 4-5 Tahun di TKK St. Clara Wudu: Analysis of the Reading Literacy Ability of Children Aged 4-5 Years at TKK St. Clara Wudu - Ngura, Elisabeth Tantiana; Yasinta Maria Fono; Martha Malo (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2024)
Literacy is a person's language skills which includes the ability to listen, read, speak, and write which are used to communicate in different ways according to their goals. Many problems in literacy are caused by a lack of habituation that is done early on. This study aims to analyze and describe how children's literacy skills in TKK St. Clara Wudu at the age of 4-5 years totaled 15 children through online learning during the current pandemic. This research is a type of qualitative descriptive research, with research subjects namely children in TKK St. Clara Wudu. Data collection techniques used are; observation, interview, and documentation. The data analysis used is in the form of descriptive analysis, which includes three paths namely; data reduction, data presentation, and conclusion drawing. The conclusion obtained is that the average listening ability of children is in the category of developing according to expectations (BSH) with an average number of 58. Based on the results of the research and discussion, it can be concluded as follows. 1. The initial reading literacy level of children in the early childhood kindergarten group A at St. Clara Wudu, Nagekeo District is in good criteria 2. The results of observations and interviews show that teachers and schools have planned and implemented literacy learning from the Collaborative Education service program with INOVASI. The results of these activities have been implemented in kindergartens in Boawae District. If a child can read well, other literacy skills such as speaking, writing and listening will also get better. The results of observations and interviews show that teachers and schools have planned and implemented literacy learning from the Collaboration Education program with INOVASL. The results of these activities have been implemented in TKK in Boawae District   ABSTRAK Literasi adalah kemampuan berbahasa seseorang yang mencakup kemampuan menyimak, membaca, berbicara, dan menulis yang digunakan untuk berkomunikasi dengan cara yang berbeda-beda sesuai dengan tujuannya. Banyaknya permasalahan dalam literasi diakibatkan kurangnya pembiasaan yang dilakukan sejak dini. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan bagaimana kemampuan literasi anak di TKK St. Clara Wudu pada Usia 4-5 tahun berjumlah 15 anak melalui pembelajaran daring di masa pandemik sekarang ini. Penelitan ini merupakan jenis penelitian deskriptif kualitatif, dengan subjek penelitian yakni anak di TKK St. Clara Wudu. Teknik pengumpulan data yang digunakan berupa; observasi, wawancara, dan dokumentasi. Analisis data yang digunakan berupa analisis deskriptif, yang mencakup tiga jalur yaitu; reduksi data, penyajian data, serta penarikan kesimpulan. Kesimpulan yang diperoleh yaitu, kemampuan menyimak rata-rata anak berada dalam kategori berkembang sesuai harapan (BSH) dengan jumlah rata-rata 58. Berdasarkan hasil penelitian dan pembahasan, maka dapat disimpulkan sebagai berikut. 1. Tingkat literasi membaca permulaan anak di kelompok TK anak usia dini kelompok A di TKK St. Clara Wudu, Kabupaten Nagekeo ada pada kriteria baik 2. Hasil observasi dan wawancara menunjukkan bawa guru dan sekolah telah merencanakan dan melaksanakan pembelajaran literasi dari program dinas Pendidikan Kerjasama dengan INOVASI. Hasil kegiatan tersebut, telah diimplementasikan di TK yang ada di Kecamatan Boawae. Apabila seorang anak sudah dapat membaca dengan baik maka kemampuan literasi lainnya seperti berbicara, menulis dan menyimak juga semakin baik lagi. Hasil  observasi  dan  wawancara  menunjukkan bawa  guru  dan  sekolah telah   merencanakan    dan   melaksanakan    pembelajaran   literasi   dari program  dinas Pendidikan  Kerjasama  dengan INOVASL Hasil kegiatan tersebut, telah diimplementasikan  di TKK yang ada di Kecamatan Boawae